Comparing the Wave Characteristics of Breakdown Pulses of the Lightning Waveforms in the Himalayan Region - Pitri Bhakta Adhikari; Aashutosh Adhikari (The Scientific World Journal)
We have analyzed the breakdown pulse train with or without the main event in this paper. Among the selected 81 flashes, 36 flashes are starting positively, and 45 are starting negatively. Also, 58 flashes contain positive pulses, and 67 flashes contain negative pulses, whereas 44 flashes contain both positive and negative pulses. Among these 81 flashes, 22 flashes follow the main events, and the rest are isolated events. In this study, we got the main duration of PB pulses as 1.94 ms and the time interval between the breakdown pulse and return stroke as 61.49 ms. On taking each pulse train, we found the rise time to be 2.6 μs, zero-crossing time 14.95 μs, and the time interval between pulses 199.3 μs. The largest pulse amplitude ratio in the preliminary breakdown pulse to the main event return stroke was 0.43.